SME’s financial literacy: An overview based on demographic aspects - Iramani Iramani; Tatik Suryani; Lindiawati Lindiawati (Universitas Hayam Wuruk Perbanas, 2017)
This study attempts to examine the financial literacy level of SME’s owner in East Java based on demographic aspect. The sample was taken from 65 SME’s in East Java which produce prominent local product. The data were collected by using survey method and deep interview. They were analyzed using descriptive explorative and also cross tabulation for examining SME’s financial literacy based on demographic attribute. Research found that that the financial literacy score of SME’s owner in East Java is good enough, where they have average score 55.8 with the same score of median and mode 66.7. Majority weakness of SME’s owner is the literacy on SME understanding of net asset and insurance premium. Otherwise, whole SME’s owner is fully understood that financial knowledge is so useful for the SME. Other finding shows that there is a relationship between financial literacy’s level and SME’s owner on demographic aspect such as gender, education, the business time established. It can be concluded that demographic aspects determine the financial literacy level of SME’s owner